Achievement of Creative Economy Dimensions in Regional Development Indonesia in 2021 - Anisa Nur Jannah; Ekaria Ekaria (Proceedings of The International Conference on Data Science and Official Statistics, 2023)
So far, measurement for knowing development of creative economy in Indonesia has only seen from GDP and number of workers. Even though there are many other factors used to determine development of creative economy that are not included in these two measurements. Therefore, this study aims to develop a measurement that can be used as a tool for assessing and analyzing the state of creative economy in 34 provinces in Indonesia and for comparison. Data used is secondary that sourced from BPS and several agencies. Creative Economy Index (CEI) refers to Global Innovation Index which is composed from seven dimensions, institution, human capital and research, infrastructure, market sophistication, business sophistication, knowledge and technology outputs, creative outputs. Analysis method used is factor analysis to validate dimensions of CEI based on their indicators. Results showed that Indonesia`s CEI is relatively low. Dimension with highest achievement is institution, while lowest achievement is market sophistication. When compared by region, CEI in Western Region is higher than Eastern Region. There are also similarities with HDI and ICT-DI.